Simultaneous extraction of phenolics and essential oil from peppermint by pressurized hot water extraction - Cam, Mustafa; Yuksel, Esma; Alasalvar, Hamza; Basyigit, Buelent; Sen, Huelya; Yilmaztekin, Murat; Ahhmed, Abdulatef; Sagdic, Osman (SPRINGER INDIA, 2019)
Phenolics and essential oil of peppermint were obtained by pressurized hot water extraction (PHWE). The best extraction conditions were found to be 130 degrees C for temperature, 10min for extraction time, and 3 cycles for extraction number. There were no statistically significant differences between 130 and 160 degrees C in terms of essential oil content. Total phenolic contents (TPC) of the extracts were higher at 160 degrees C than that of 130 degrees C. However, further HPLC analysis of the extracts revealed that hydrolysis and/or decomposition of phenolics were observed in the extracts obtained at 160 degrees C. The main phenolic of peppermint was determined as eriocitrin by HPLC-DAD, while menthol was the dominant component in essential oil fraction of peppermint by GC-FID. The present study demonstrated that PHWE was a suitable technique for simultaneous extraction of phenolics and essential oil from peppermint. The technique might be used as an analytical extraction tool for determination of phenolics and essential oil. Moreover, the extracts of PHWE could directly be evaluated for the enrichment of liquid food formulations or be transformed into solid form by suitable techniques such as spray drying for easy storage and subsequent enrichment of food products.
Keywords: Peppermint; Phenolics; Pressurized hot water extraction; Menthol; Eriocitrin; ANTIOXIDANT CAPACITY; AROMA COMPOUNDS; OPTIMIZATION; INHIBITION; TEAS; Food Science & Technology